Crisi identitaria e speculazione panarabista nella Tunisia post-rivoluzionaria: che ne facciamo della tunisianità e della lingua tunisina? - Alfonso Campisi (EtnoAntropologia)
This text speaks about two very important problems existing in Tunisia, after revolution: identity and language. The problem about Tunisian identity is very present in Tunisia, because the article 38 of constitution speaks about Arabic-Muslim identity, but that, it is not correspond to the reality, because we have to talk about  a specific identity character of the country. “Tunisianity”, it’s the wright answer to the article 38.